Activated carbons prepared from industrial pre-treated cork: Sustainable adsorbents for pharmaceutical compounds removal (Chemical Engineering Journal, 2014)
Industrial pre-treated cork – granules of expanded corkboard, prepared from renewable biomass – was used for the first time as precursor for the preparation of eco-friendly activated carbons by chemical (K2CO3 and KOH) and physical (steam) activation. Samples with different textural (microporosity/ micro + mesoporosity) and surface chemistry (acidic/basic) were obtained. In the best compromise between porosity development/preparation yield, apparent surface areas P900m2 g?1 were attained. Selected samples were assayed as adsorbents for the removal of pharmaceutical compounds (ibuprofen, paracetamol, acetylsalicylic acid, clofibric acid, caffeine and iopamidol). Kinetic results show that the steam activated carbon removes all the pharmaceutical compounds under study with removal efficien- cies between 40% and 90%. Ibuprofen equilibrium adsorption isotherms showed that sample chemically activated with KOH at 800 ?C presents higher adsorption capacity (174.4 mg g?1) and affinity for this target molecule than the steam activated and commercial samples. The overall results reveal that the lab-made carbons have adequate properties for pharmaceutical compounds removal, the results compar- ing favourably to those obtained with samples commercialized for water treatment purposes

Cork stoppers as an effective sorbent for water treatment: the removal of mercury at environmentally relevant concentrations and conditions (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2014)
The technical feasibility of using stopper-derived cork as an effective biosorbent towards bivalent mercury at environmentally relevant concentrations and conditions was evaluated in this study. Only 25 mg/L of cork powder was able to achieve 94 % of mercury removal for an initial mercury concentration of 500 mu g/L. It was found that under the conditions tested, the efficiency of mercury removal expressed as equilibrium removal percentage does not depend on the amount of cork or its particle size, but is very sensitive to initial metal concentration, with higher removal efficiencies at higher initial concentrations. Ion exchange was identified as one of the mechanisms involved in the sorption of Hg onto cork in the absence of ionic competition. Under ionic competition, stopper-derived cork showed to be extremely effective and selective for mercury in binary mixtures, while in complex matrices like seawater, moderate inhibition of the sorption process was observed, attributed to a change in mercury speciation. The loadings achieved are similar to the majority of literature values found for other biosorbents and for other metals, suggesting that cork stoppers can be recycled as an effective biosorbent for water treatment. However, the most interesting result is that equilibrium data show a very rare behaviour, with the isotherm presenting an almost square convex shape to the concentration axis, with an infinite slope for an Hg concentration in solution around 25 mu g/L.

Use of cork powder and granules for the adsorption of pollutants: a review. (Water research, 2012)
Cork powder and granules are the major subproducts of the cork industry, one of the leading economic activities in Portugal and other Mediterranean countries. Many applications have been envisaged for this product, from cork stoppers passing through the incorporation in agglomerates and briquettes to the use as an adsorbent in the treatment of gaseous emissions, waters and wastewaters. This paper aims at reviewing the state of the art on the properties of cork and cork powder and their application in adsorption technologies. Cork biomass has been used on its original form as biosorbent for heavy metals and oils, and is also a precursor of activated carbons for the removal of emerging organic pollutants in water and VOCs in the gas phase. Through this literature review, different potential lines of research not yet explored can be more easily identified.